Islam dan Tata Negara: Pemikiran Sosial Politik Muhammad Natsir - Khumaidi, Khumaidi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
The purpose of this research is to explain Natsirâs thought on state, its implications and the factors which influence his thoughts. This research employs historical approach. Formerly, Natsir was the proponent of those who accepted The Five Pillars (Pancasila). But not long after that he declared his opposition against this sole-principle (azas Tunggal). He is in the opinion that Muslims has had a definite, clear and perfect ideology, that is Islam. He dreamed of the Islamic-based ideologt in Indonesia. His thinking brings him about into jails for several time by the ruling party at his given time and his party, Masyumi, was banned as well. The factors that changed Natsirs thoughts were the conditions of social-politics, his religious informal education background of radical Islam and also his struggle in the name of Masyumi party.